2016
DOI: 10.1155/2016/6418710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Smartphone Applications for Cardiopulmonary Resuscitation Training in South Korea

Abstract: Objective. There are many smartphone-based applications (apps) for cardiopulmonary resuscitation (CPR) training. We investigated the conformity and the learnability/usability of these apps for CPR training and real-life supports. Methods. We conducted a mixed-method, sequential explanatory study to assess CPR training apps downloaded on two apps stores in South Korea. Apps were collected with inclusion criteria as follows, Korean-language instruction, training features, and emergency supports for real-life inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
0
27
1
1
Order By: Relevance
“…Therefore we decided to focus only on apps offering real-time support. This is in contrast to the study of Ahn and colleagues, who concentrating solely on CPR-training apps [17].…”
Section: Comparison With Prior Workcontrasting
confidence: 64%
See 1 more Smart Citation
“…Therefore we decided to focus only on apps offering real-time support. This is in contrast to the study of Ahn and colleagues, who concentrating solely on CPR-training apps [17].…”
Section: Comparison With Prior Workcontrasting
confidence: 64%
“…Cognitive aids, which are based on medical guidelines, are more and more accepted in healthcare [16]. Ahn and colleagues described, that the total number of downloads for CPR training apps is about several hundred thousand [17]. However, the field is getting more and more complex and unmanageable [18].…”
Section: Introductionmentioning
confidence: 99%
“…The SUS is a standardized questionnaire commonly used to assess participants' perceptions of usability of an electronic system or device [31,32]. The scale consists of a 10-item questionnaire and each item is rated on a 5-point Likert scale ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The scores are added together and multiplied by 2.5 to get the final score, with a range of 0 to 100. A score of above 68 is considered above average in the evaluation of mobile health apps [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ahn et al [28], for example, in which five cardiopulmonary resuscitation training apps were assessed, only one app had a mean usability score above 80 (81.17±19.01). Lacerda et al [29], who compared two cardiology telediagnosis interfaces, found a score below 80 for both (77.5 and 58.8).…”
Section: Comparison With Prior Workmentioning
confidence: 99%